2007
DOI: 10.2522/ptj.20060229
|View full text |Cite
|
Sign up to set email alerts
|

Game-based Exercises for Dynamic Short-Sitting Balance Rehabilitation of People With Chronic Spinal Cord and Traumatic Brain Injuries

Abstract: Background and Purpose Goal-oriented, task-specific training has been shown to improve function; however, it can be difficult to maintain patient interest. This report describes a rehabilitation protocol for the maintenance of balance in a short-sitting position following spinal cord and head injuries by use of a center-of-pressure–controlled video game–based tool. The scientific justification for the selected treatment is discussed. Case Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 31 publications
2
94
0
3
Order By: Relevance
“…[14][15][16] Presumably, an increase in cortical control of muscles after incomplete SCI might allow functional recovery through the development of alternative movement strategies. 25 As a result, the motor programs for balance control strategies, provided by task-specific training, seemed to be effective and could affect the final outcome of the participants in our study.…”
Section: Improved Balance Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] Presumably, an increase in cortical control of muscles after incomplete SCI might allow functional recovery through the development of alternative movement strategies. 25 As a result, the motor programs for balance control strategies, provided by task-specific training, seemed to be effective and could affect the final outcome of the participants in our study.…”
Section: Improved Balance Functionmentioning
confidence: 99%
“…7 Although further studies are needed to investigate a potential association between positive results obtained from laboratory force plate measures and clinical and functional outcomes, 6,9 it has been shown that the main positive effect of such training on postural control can be attributed to sensorimotor integration 5,[10][11][12][13] as well as the coordination improvement because of the task specificity of training. 14,15 In the SCI population, benefits of game-based exercises 16 and virtual reality 3 have been suggested for dynamic sitting balance. These studies have shown their potential for substantial improvements in sitting balance through the inclusion of functional approaches in the training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, balance dysfunction is a very important issue in the elderly. Numerous therapeutic interventions have been attempted in order to improve the postural control ability of elderly adults and various types of patients 6,8,9,30) . Our findings show that mental practice with motor imagery can provide an effective and safe training method for individuals with balance dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Balance-related problems lead to considerable health problems and social incur services costs, because of the patient's dependence on basic functional activities 5) . In order to improve balance ability, many studies have adopted a wide range of training methods involving balance training with visual feedback, muscle strength training, plyometric, virtual reality, and mental training [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%